Comparative Study of Traditional and Environmentally Friendly Zinc Sources Applied in Alkaline Fluvisol Soil: Lettuce Biofortification and Soil Zinc Status - Raquel Ortiz; Gabriel Gascó; Ana Méndez; Laura Sanchez-Martín; Ana Obrador; Patricia Almendros (Agronomy, 2023)
The use of highly effective sources of zinc (Zn) in alkaline agricultural soils is essential to achieve crop biofortification, maintain crop quality, and avoid potential environmental risks. This research examines the efficacy of environmentally friendly Zn complexes (citric acid, CIT and glycine, GLY) compared to a traditional source (ZnSO4) for the lettuce cultivation in alkaline soil. The effectiveness of Zn sources was assessed based on the concentration of total and soluble Zn, plant biomass, and contents of photosynthetic pigments. The soil Zn status was also evaluated. While all Zn sources (Zn-GLY, Zn-CIT, and ZnSO4) showed positive effects on lettuce growth, Zn-GLY exhibited the highest efficacy. This source exhibited increases of 230%, 502%, 296%, and 409% over the control in Zn concentration in young and mature leaves, soluble Zn, and Zn uptake, respectively. Zn-GLY also resulted in a 371% increase in soil exchangeable Zn concentration, compared to the control treatment. Our findings indicate that Zn-GLY could replace the traditional ZnSO4 treatment, as it achieved high Zn biofortification of lettuce and a high concentration of Zn available in the medium-long term in the soil. The beneficial effect of the chelating agent GLY on plant chlorophyll and carotenoid contents is also remarkable.